The Inhibition of Silica-Induced Lung Inflammation by Dexamethasone as Measured by Bronchoalveolar Lavage Fluid Parameters and Peroxynitrite-Dependent Chemiluminescence - K. Van Dyke; J. M. Antonini; L. Wu; Z. Ye; M. J. Reasor (The National Institute for Occupational Safety and Health (NIOSH), 1995)
The inhalation of silica has been shown to produce a dramatic inflammatory and toxic response within the lungs of humans and· laboratory animals. Currently, no effective treatment exists for workers who may have been exposed to the inhalation of silica. The objective of this study was to develop an animal model in which we could evaluate the effect that anti-inflammatory steroids have on the acute silica-induced pulmonary inflammatory response. Male Fischer 344 rats were pretreated with either dexamethasone (2 mg/kg) or saline vehicle (i.p.) on days 1, 3, and 5. On day 6, the animals from the two groups were then intratracheally instilled with either silica (20 mg/0.5 ml saline vehicle) or saline vehicle (0.5 ml). Twenty-four hours after the instillations in the non-steroid group, significant increases occurred in total protein, total number of cells, neutrophils, and lymphocytes recovered from the lungs of animals treated with silica compared to saline controls. Silica also caused dramatic increases in the luminol-dependent chemiluminescence (LDCL) of lung tissue and bronchoalveolar lavage (BAL) cells. The LDCL reaction was markedly decreased by either superoxide dismutase (SOD) or N-nitro-L-arginine methyl ester hydrochloride (L-NAME). SOD is involved in the enzymatic breakdown of superoxide anion, while L-NAME, a nitric oxide (NO) synthase inhibitor, prevents the formation of NO. When the superoxide anion and NO react, they form the highly oxidizing substance peroxynitrite. This study then implicates peroxynitrite as an agent which may be involved in the silica-induced oxidant lung injury. When the animals were pretreated with the steroid dexamethasone, there was a complete protection against the biochemical, cellular, and chemiluminescent indices of damage caused by silica. The mechanism in which the steroid protects the lung from damage may be due to the ability of dexamethasone to block the induction of NO synthase. With further study in animals, the anti-inflammatory steroids may be useful in the treatment of silicainduced lung injury.